Study of Characteristic Equation of the Elastic Stress Field near Bimaterial Notche - Arabi, H.; Mirsayar, M.M.; Samaei, A.T.; Darandeh, M. (Проблемы прочности, 2013)
Fracture occurs at interface corners due to stress singularity which generates as a result of material discontinuity and geometrical configuration. In elastic stress field near a bimaterial notch tip, eigenvalues extracted from Airy’s stress function approach determine the order of singularity. In this paper, the characteristic equation of elastic stress field near bimaterial notches is investigated. The study is done on singular eigenvalues as well as the first non-singular eigenvalue which has not been well studied before. First, different combination of materials and geometrical configurations for two of the most applicable paths in the Bogy diagram (β = 0, β = α/4) were studied and the results were comprehensively discussed. It was shown that the geometrical and materials configurations near a bimaterial notch tip can significantly affect on the stress singularity near these corners. Finally, the areas between two lines β = 0 and β = α/4 in the Bogy diagram with high stress singularities were determined and discussed for both the first and second singular eigenvalue.